Photoprotective measures of selected sunscreens and their antioxidant adjuvantion effects in the Malaysian climate. - Khamsiah N; Lai, NS; Nurfarhanim M; Nor Aimi AR; Mohd Syazwan Che Seman; Goon, JA (Penerbit UKM, 2012)
The Malaysian skincare industry is growing rapidly with a vast number of new sunscreens being produced annually. Inadequate skincare regulations and lack of enforcement have resulted in the overrating of sunscreens’ quality. The objectives of this study were to evaluate the efficacy and safety of the local and international sunscreens and to determine the effects of adding concentrated antioxidants into them. Three local and three internationally manufactured sunscreens were tested for the in vitro Ultraviolet A protection factor (UVAPF), Sun Protection Factor (SPF) and photostability. The creams were spread onto roughened polymethylmethacrylate plates where the absorbance was measured using a spectrophotometer before and after two hours of sunlight irradiation. The procedure was repeated combining available concentrated vitamin C and E creams. International sunscreens were found to have more accurate SPF labels (p=0.009) while local sunscreens were found to be more photostable (p=0.003). However, both sunscreens had inadequate UVAPF (p=0.471). Vitamin C enhanced the SPF values (p= 0.04) of both groups of sunscreens while vitamin E enhanced their photostability (p=0.000). Interestingly, combining vitamins C and E rich creams with the sunscreens had no effect on the SPF and UVAPF values as compared to the use of a single vitamin. More importantly, the combination of vitamins decreased the photostability (p=0.002) of sunscreens as compared to the addition of vitamin E alone. In conclusion, photoprotection is best achieved when sunscreens are used together with creams containing either vitamin C or E alone.